Ionisation gradient of low resistivity soils and liquids - Nor, N.M. (2006)
The effects of moisture contents in sand (from 1% to 10%), grain size (medium and fine), impulse polarity and earth electrode's dimension (hemispherical and parallel-plate test cell) on the threshold electric field, E-c value, have been presented in a previous work [1]. In that study [1], the E-c value is obtained when two current peaks were observed. However, no E-c value is obtained for low resistivity test media (resistive liquid medium, sand with large percentage of water content=15%, salt with different percentage of water content, and sand-salt soil mixtures [1,2], since there was no second current peak was obtained in those test media. This paper is therefore to obtain the E-c value for these low resistivity test media. Using the available voltage and current traces from previous study [2], for the first time the E-c is taken when v-i curve starts to form a loop. It was found that the E-c of low resistivity test media are within the range of E-c suggested in previous studies [1-6], which are from 1.3kV/cm to 20kV/cm.